Multichannel Strategies for Managing the Profitability of Business-to-Business Customers. (June 2019) - Lawrence, Justin M.; Crecelius, Andrew T.; Scheer, Lisa K.; Patil, Ashutosh
As business-to-business customers increasingly use online channels, sellers must reconsider strategic investments in at least two areas: the salesperson channel, which faces the threat of substitution, and customer-specific discounts, which may be more precisely targeted. The authors draw on communication theory to posit that a customer's search and purchasing in the seller's online channels interact positively with both salesperson contact and customer-specific discounts to drive the seller's customer-level sales and profit return on these investments. A multimethod approach using a complex data set from a large industrial seller provides broad support for hypothesized effects. Two post hoc experiments reveal how online and salesperson channels are complementary, together improving customer–seller communication such that the seller is better able to fulfill customer needs and reduce customer perceived risk. This research advances the multichannel and pricing literatures and offers actionable insights for business-to-business marketers, revealing how online channels can complement traditional seller investments in salespeople and customer-specific discounts.